Dampak lingkungan sosial terhadap motivasi dan prestasi belajar siswa: peran keluarga, teman, dan guru - Shofi, Ajmal Ramzani Nasywa (Maliki Interdisciplinary Journal, 2025)
The social environment plays a crucial role in shaping students' motivation and learning achievement. This article discusses conceptually the influence of the social environment which includes family factors, friendships, and the role of teachers on students' learning motivation and academic achievement. Through theoretical analysis, this article explores how family parenting, peer support, and the quality of the relationship between teachers and students can affect students' interest in learning and engagement in academic activities. With a conceptual analysis approach, this article also examines the implications of the relationship between these three components on the achievement of optimal learning outcomes. Previous research has shown that interactions between family, friends, and teachers play an important role in shaping a learning climate that supports student success. This article concludes that collaboration between family, friends, and teachers is indispensable to creating a supportive learning environment. The theoretical implications of these findings provide insight for educators and parents in building an environment conducive to the development of students' academic potential.